Implementasi Teknologi Informasi dan Komunikasi (TIK) pada Rantai Pasok Produk Pertanian: Tinjauan Literatur Sistematik - Nurzakiah, Sitty; Muhammad, Anindito; Muflikh, Yanti Nuraeni (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Information flow is a vital component of the supply chain that flows throughout the chain and involves all participants. In the era of globalization, companies are starting to change the way they communicate by applying technology. This has an impact on increasingly diverse transactions and processes, which can improve business performance through the application of ICT in the supply chain network. Previous research focuses on the relationship between the use of information technology and information exchange in the supply chain. Meanwhile, there are various types of ICT that have their respective impacts and benefits that need to be discussed simultaneously. The aim of this research is to identify the types and role of ICT in the agricultural product supply chain, and also studies of ICT application in the agricultural product supply chain. The research was conducted through a systematic literature review, using 23 literature sources. Based on the analysis results, the agricultural sector utilizes a wide range of ICT technologies, including blockchain, Internet of Things, wireless sensor networks, cloud computing, RFID, and machine learning. The use of ICT in the agricultural product supply chain has contributed to the increase in competitiveness and performance of the supply chain, through collecting accurate information in real-time and product tracking, facilitating the exchange of information between supply chain actors, increasing product value and supporting value creation, facilitate decision making, expand market access, increase efficiency and revenue. ICT in agricultural supply chains has been implemented in various countries, such as India, Senegal and Australia.